Perbandingan Tegangan Aksial Antara Jembatan Rangka Kayu Box Beam Section dan Konvensional Dari Kayu Kamper - Wijaya , Handika Setya; Oktaviastuti , Blima (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2018)
Indonesia has more than 80 thousand villages as the smallest administrative unit of the Republic of Indonesia. Each village needs at least three to four bridges to cross the river, and to access other facilities. The many bridge needs are not accompanied by the state budget allocated to the construction of bridges in villages. One alternative bridge construction is from wood material is also a renewable material. Constraints in the use of wood for building construction are the scarcity of wood with large dimensions. To overcome this problem, there is engineering wood (engineering wood), one of which is the box beam. Box beams are proven to increase the inertia of a material when compared to conventional wooden beams with the same cross-sectional area. This study aims to find a comparison of the strengths between conventional wooden bridges and wooden bridges using Camper box beam elements. The results of this study indicate that from the comparison of box beams and ordinary wood beams it turns out that the box beam produces a voltage of 0.129 MPa and a conventional beam of 0.142 MPa. Based on the results of the study it can be concluded that the box beam has a higher compressive strength than solid wood with the same cross-sectional area. And can be a recommendation for the selection of short span bridge structures for Rural because it is more economical and strong.